Corrosion and tribocorrosion behavior of Ti–B4C composite intended for orthopaedic implants. (August 2016) - Toptan, F.; Rego, A.; Alves, A.C.; Guedes, A.
Abstract: Poor wear resistance of titanium is a major concern since relative movements due to the cyclic loads in body environment cause wear between the bone and the implant material leading to detachment of the wear debris and release of metal ions due to the simultaneous action of corrosion and wear, defined as tribocorrosion. In order to increase the tribocorrosion resistance, Grade 2 Ti matrix 24 vol% B4 C particle reinforced composites were processed by hot pressing. Corrosion behaviour was investigated by electrochemical impedance spectroscopy and potentiodynamic polarization in 9 g/L NaCl solution at body temperature. Tribocorrosion tests were performed under open circuit potential, as well as under potentiodynamic polarization using a reciprocating ball-on-plate tribometer. Results suggested that the addition of B4 C particles provided lower tendency to corrosion and lower corrosion kinetics under sliding, along with significantly reduced wear loss, mainly due to the load carrying effect given by the reinforcement particles.